Supercapacitor performance of activated carbon derived from rotten carrot in aqueous, organic and ionic liquid based electrolytes - Ahmed, Sultan; Ahmed, Ahsan; Rafat, M. (Journal of Saudi Chemical Society, 2018)
In this work, we report the synthesis of porous activated carbon (AC). AC was derived from rotten carrot, at different values of activating temperature under inert atmosphere, employing chemical activation method and ZnCl2 as activation agent. On the basis of results observed by surface area and pore size analysis, effect of activation temperature on synthesized AC was determined. Other material properties such as morphology, thermal stability, vibrational response, and crystal structure of prepared AC were studied using standard techniques of material characterization. Further, the electrochemical performance of synthesized AC was studied as an electrode, in aqueous, organic and ionic liquid based electrolyte. It was found that the synthesized AC based electrode exhibits highest specific capacitance (135.5 F g−1 at 10 mHz) in aqueous electrolyte and highest specific energy (29.1 Wh kg−1 at 2.2 A g−1) and specific power (142.5 kW kg−1 at 2.2 A g−1) in ionic liquid based electrolyte. This shows the suitability of synthesized material for use in energy storage applications.